Era uma vez... Representações sociais e letramento no ensino de Língua Portuguesa - Chaves, Lorena Lopes (2020)
Literacy is a concern with reading and writing for many scholars. Fairy tales are works designed for children. Joining these two points, it is possible to extract much more than entertainment in reading such works. This research sought, therefore, to use fairy tales in order to raise the level of literacy of students, who had contact with works that present princesses of different styles, checking if stereotypes were formed by students, how it was reproduced in their writing and if it impacted the image they conceive of modern women. The objective was to identify the role of women built by 9th grade students from a public school in Fortaleza. To this end, the tales Snow White and the Seven Dwarfs, Beauty and the Beast and The Princess and the Frog were used. In search of these results, some activities with verbal, non-verbal and multimedia texts were carried out. Theoretical assumptions were supported by theories about literacy, the Social Representations Theory, Bakhtin's concept of language, the theory of genres and fairy tales. It was found that there was an achievement of the objectives and a redefinition of the social role of women.